Paleotemperature records of the Last Glacial Maximum from noble gases in groundwater - Seltzer, Alan; Ng, Jessica; Aeschbach, Werner; Kipfer, Rolf; Kulongoski, Justin T.; Severinghaus, Jeffrey P.; Stute, Martin; Wieser, Martin; Deshpande, R. D.; Van Khoi, Le; Schlosser, Peter; Love, Andy; et al. (PANGAEA - Publishing Network for Geoscientific and Environmental Data, 2021)
Seltzer, Alan; Ng, Jessica; Aeschbach, Werner; Kipfer, Rolf; Kulongoski, Justin T; Severinghaus, Jeffrey P; Stute, Martin; Wieser, Martin; Deshpande, R D; Van Khoi, Le; Schlosser, Peter; Love, Andy; Herczeg, Andrew; Clark, Jordan F; Simpson, Jim (2021): Paleotemperature Records of the Last Glacial Maximum from Noble Gases in Groundwater. PANGAEA, https://doi.org/10.1594/PANGAEA.929176
Gesehen am 20.05.2021
Keywords: Forschungsdaten; Datenbank